PENENTUAN HARGA JUAL MENGGUNAKAN METODE COST PLUS PRICING DENGAN PENDEKATAN VARIABEL COSTING - Fitrah, Rezandra (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
When new companies emerging in the field of business and the same product is a competition that must be faced in a healthy. Efforts to do so the company remains exis, by improving product quality, intensified the promotional, such as by determining a competitive price. The purpose of the study was to determine and analyze whether the sale pricing Starmugs Coffee products allow businesses to thrive and survive in the business competition is quite tight. This research use quantitative data that presented by a numbers. In the calculations using the Cost Plus pricing method with a variable approach for product costing drinks coffe latte, capucino, or machiatto. The results showed that the determination of the selling price and cost plus pricing method through the variable costing approach can facilitate the management in making decisions, especially in determining the selling price of the product is to calculate the variable cost plus a mark-up, besides that in the event of changes in variable costs, management can immediately adjusting the selling price without having to calculate the overall cost.Keywords : sales price, costing variable, cost Plust pricing method.